N-Acetylcysteine Decreases Myocardial Content of Inflammatory Mediators Preventing the Development of Inflammation State and Oxidative Stress in Rats Subjected to a High-Fat Diet - Klaudia Sztolsztener; Wiktor Bzdęga; Katarzyna Hodun; Adrian Chabowski (International Journal of Inflammation)
Arachidonic acid (AA) is a key precursor for proinflammatory and anti-inflammatory derivatives that regulate the inflammatory response. The modulation of AA metabolism is a target for searching a therapeutic agent with potent anti-inflammatory action in cardiovascular disorders. Therefore, our study aims to determine the potential preventive impact of N-acetylcysteine (NAC) supplementation on myocardial inflammation and the occurrence of oxidative stress in obesity induced by high-fat feeding. The experiment was conducted for eight weeks on male Wistar rats fed a standard chow or a high-fat diet (HFD) with intragastric NAC supplementation. The Gas-Liquid Chromatography (GLC) method was used to quantify the plasma and myocardial AA levels in the selected lipid fraction. The expression of proteins included in the inflammation pathway was measured by the Western blot technique. The concentrations of arachidonic acid derivatives, cytokines and chemokines, and oxidative stress parameters were determined by the ELISA, colorimetric, and multiplex immunoassay kits. We established that in the left ventricle tissue NAC reduced AA concentration, especially in the phospholipid fraction. NAC administration ameliorated the COX-2 and 5-LOX expression, leading to a decrease in the PGE2 and LTC4 contents, respectively, and augmented the 12/15-LOX expression, increasing the LXA4 content. In obese rats, NAC ameliorated NF-κB expression, inhibiting the secretion of proinflammatory cytokines. NAC also affected the antioxidant levels in HFD rats through an increase in GSH and CAT contents with a simultaneous decrease in the levels of 4-HNE and MDA. We concluded that NAC treatment weakens the NF-κB signaling pathway, limiting the development of myocardial low-grade inflammation, and increasing the antioxidant content that may protect against the development of oxidative stress in rats with obesity induced by an HFD.